Intelligence and Self-Esteem as Correlates of Marital Success Among Married Couples in Sokoto Metropolis: Implications for Counselling - Abdullahi Bello Tambuwal; Buhari Lawal; Ahmed Bello (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
ABSTRACT The main thrust of the study was to find out the relationship among emotional intelligence, self-esteem communication styles and marital success among couples in Sokoto Metropolis with a view to identifying its implications for counselling. The study was a correlational type and has a total population of 884656 married individuals and a sample of 384 as determined by research advisors (2006) table for determining sample size from a given population. The study adopted random sampling technique in selecting the target participants at the field. Questionnaire developed by Tambawal (2021) titled “Emotional Intelligence, Self-esteem and Marital Success Questionnaire” was used (EISECSMSQ) with construct and content validity as ascertained by experts in management evaluation. The reliability of 0.72 which was obtained through test, re-test method of estimating reliability index of the instrument. Two null hypotheses were formulated and tested using Pearson Product Moment Correlation Coefficient Formula for hypotheses. Results showed that there was significant relationship between Emotional Intelligence and Marital Success; Self-Esteem and Marital Success. However, Emotional Intelligence was found to be a better predictor of marital success among the independent variables. The study therefore, concludes that there was significant positive relationship between emotional intelligence and marital success; self-esteem and marital success. Among recommendations offered were married couples should be exposed to emotional intelligence components and skills during pre-marital and marital counselling sessions. Keywords: Emotional Intelligence, Self-esteem and Marital Success